Contribution of the Interdecadal Pacific Oscillation to twentieth-century global surface temperature trends - Meehl, Gerald A.; Hu, Aixue; Santer, Benjamin D.; Xie, Shang-Ping (Nature climate change, 2016)
Natural multidecadal climate variability contributes to global mean surface temperature trends. This study quantifies those from the Interdecadal Pacific Oscillation, finding that the largest contributions are during the positive phase, which accelerates warming. Longer-term externally forced trends in global mean surface temperatures (GMSTs) are embedded in the background noise of internally generated multidecadal variability 1 . A key mode of internal variability is the Interdecadal Pacific Oscillation (IPO), which contributed to a reduced GMST trend during the early 2000s 1 , 2 , 3 . We use a novel, physical phenomenon-based approach to quantify the contribution from a source of internally generated multidecadal variability—the IPO—to multidecadal GMST trends. Here we show that the largest IPO contributions occurred in its positive phase during the rapid warming periods from 1910–1941 and 1971–1995, with the IPO contributing 71% and 75%, respectively, to the difference between the median values of the externally forced trends and observed trends. The IPO transition from positive to negative in the late-1990s contributed 27% of the discrepancy between model median estimates of the forced part of the GMST trend and the observed trend from 1995 to 2013, with additional contributions that are probably due to internal variability outside of the Pacific 4 and an externally forced response from small volcanic eruptions 5 . Understanding and quantifying the contribution of a specific source of internally generated variability—the IPO—to GMST trends is necessary to improve decadal climate prediction skill.